2012
DOI: 10.1186/1475-2859-11-62
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thioredoxin/glutaredoxin-mediated L-cysteine synthesis from S-sulfocysteine increases L-cysteine production in Escherichia coli

Abstract: BackgroundEscherichia coli has two L-cysteine biosynthetic pathways; one is synthesized from O-acetyl L-serine (OAS) and sulfate by L-cysteine synthase (CysK), and another is produced via S-sulfocysteine (SSC) from OAS and thiosulfate by SSC synthase (CysM). SSC is converted into L-cysteine and sulfite by an uncharacterized reaction. As thioredoxins (Trx1 and Trx2) and glutaredoxins (Grx1, Grx2, Grx3, Grx4, and NrdH) are known as reductases of peptidyl disulfides, overexpression of such reductases might be a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 17 publications
2
61
0
Order By: Relevance
“…The knowledge of the relative abundance and regulation by effectors of the two isozymes during infection is a relevant missing information that can contribute to the pharmacological exploitation of these targets. For example, it has been recently shown that the activity of OASS-B on thiosulfate could represent an energy saving path to cysteine biosynthesis and could be preferred in metabolic conditions where the conservation of ATP and NADPH is important [117]. In addition, very recently, works by Hayes and coworkers [118], [119], identified OASS as the activating factor for a toxin that controls contact-dependent growth inhibition in E.coli .…”
Section: Resultsmentioning
confidence: 99%
“…The knowledge of the relative abundance and regulation by effectors of the two isozymes during infection is a relevant missing information that can contribute to the pharmacological exploitation of these targets. For example, it has been recently shown that the activity of OASS-B on thiosulfate could represent an energy saving path to cysteine biosynthesis and could be preferred in metabolic conditions where the conservation of ATP and NADPH is important [117]. In addition, very recently, works by Hayes and coworkers [118], [119], identified OASS as the activating factor for a toxin that controls contact-dependent growth inhibition in E.coli .…”
Section: Resultsmentioning
confidence: 99%
“…Formation of S-sulfocysteine from thiosulfate would thus provide a salvage pathway whereby some of the sulfur could be rescued by incorporation into L-cysteine. S-sulfocysteine, generated from thiosulfate by S-sulfocysteine synthases, has been postulated as an intermediate of an alternative route to L-cysteine biosynthesis in Rhodospirillum tenue (31), Salmonella enterica serovar Typhimurium (32), and E. coli (33). In the last case, it was shown that thioredoxin and/or NrdH is involved in the reduction of S-sulfocysteine to cysteine and sulfite.…”
Section: Discussionmentioning
confidence: 99%
“…CysK catalyzes the final reaction of l ‐cysteine synthesis , and its overexpression could enhance the productivity of l ‐cysteine and serine‐rich proteins . On the other hand, CysK is also related to multiple physiological processes, including contact‐dependent growth inhibition , quorum sensing , and stress response .…”
Section: Disscusionmentioning
confidence: 99%
“…In E. coli and Salmonella typhimurium , CysK is composed of two identical 34 kDa subunits ; cysK and other genes relevant to the l ‐cysteine biosynthesis are scattered on the chromosome . Overexpression of CysK could enhance productivity of l ‐cysteine and serine‐rich proteins in E. coli . CysK also plays an essential role in bacterial contact‐dependent growth inhibition .…”
Section: Introductionmentioning
confidence: 99%